A Simple Method for Estimating the Strength of Natural Selection on Overlapping Genes. (31st December 2014) - Wei, Xinzhu; Zhang, Jianzhi
Abstract : Overlapping genes, where one DNA sequence codes for two proteins with different reading frames, are not uncommon in viruses and cellular organisms. Estimating the direction and strength of natural selection acting on overlapping genes is important for understanding their functionality, origin, evolution, maintenance, and potential interaction. However, the standard methods for estimating synonymous ( d S ) and nonsynonymous ( d N ) nucleotide substitution rates are inapplicable here because a nucleotide change can be simultaneously synonymous and nonsynonymous when both reading frames involved are considered. We have developed a simple method that can estimate d N / d S and test for the action of natural selection in each relevant reading frame of the overlapping genes. Our method is an extension of the modified Nei-Gojobori method previously developed for nonoverlapping genes. We confirmed the reliability of our method using extensive computer simulation. Applying this method, we studied the longest human sense–antisense overlapping gene pair, LRRC8E and ENSG00000214248 . Although LRRC8E (leucine-rich repeat containing eight family, member E) is known to regulate cell size, the function of ENSG00000214248 is unknown. Our analysis revealed purifying selection on ENSG00000214248 and suggested that it originated in the common ancestor of bony vertebrates.